Five‐year survival impact of adjuvant anti‐ PD ‐1 therapy in a nationwide cohort of stage III melanoma - Marie B. Weitemeyer; Neel M. Helvind; Shawez Khan; Pernille Bidstrup; Karina D. Steffensen; Adam Andrzej Luczak; Lars Bastholt; Henrik Schmidt; Inge Marie Svane; Marco Donia; Lisbet R. Hölmich; Eva Ellebaek (Journal of the European Academy of Dermatology and Venereology, 2026)
Abstract Background Adjuvant anti‐PD‐1 therapy improves recurrence‐free survival in resected stage III melanoma, but its impact on survival remains uncertain. Objective To evaluate the association of adjuvant anti‐PD‐1 therapy with overall survival (OS) and melanoma‐specific mortality (MSM) in patients with stage III melanoma. Methods Five‐year OS and MSM were compared between stage III melanoma patients diagnosed before (pre‐cohort: June 2016–May 2018, n = 450) and after (post‐cohort: January 2019–December 2020, n = 552) implementation of adjuvant anti‐PD‐1 in Denmark. Post‐cohort patients receiving adjuvant anti‐PD‐1 were propensity score‐matched to pre‐cohort patients. Results Median follow‐up exceeded 5 years in both cohorts. At the population level, no difference in 5‐year OS or MSM was demonstrated between the total cohorts. In the post‐cohort, 297 patients (53.8%) received adjuvant anti‐PD‐1. After matching ( n = 279 per group), adjuvant anti‐PD‐1 was associated with higher 5‐year OS (80.3% vs. 71.7%; HR 0.67, 95% CI 0.47–0.95; p = 0.022). 5‐year MSM estimates were inconclusive (16.6% vs. 20.8%, HR 0.77, 95% CI 0.52–1.14; p = 0.24). Among matched patients with occult nodal disease, results were also inconclusive (OS HR 0.70, 95% CI 0.46–1.06). Sensitivity power analyses indicated that only large effects were detectable given the available events. Conclusions We were unable to demonstrate an improved survival at the population level after adjuvant anti‐PD‐1 introduction, but matched analysis showed higher OS in treated patients. However, uncertainty in disease‐specific outcomes and limited power preclude firm conclusions. Mature trial data are essential for defining the role of adjuvant therapy alongside emerging neoadjuvant strategies. Until then, carefully individualized adjuvant treatment decisions are of particular importance.